Adsorption of organics on MSC5A in supercritical CO2: chromatographic measurements & stop & go simulation - Chihara, Kazuyuki; Ito, Shingo; Nagashima, Hideo; Hikita, Masayuki; Suzuki, Ryosuke (Diffusion Fundamentals, 2011)
Chromatographic measurements were made for the adsorption of benzene, toluene and m-xylene on molecular sieving carbon (MSC) in a supercritical fluid CO2 mixed with organics. A supercritical chromatograph packed with MSC was used to detect pulse responses of the organics. Adsorption equilibria and adsorption dynamic parameters for organics were obtained by moment analysis of the response peaks. Dependences of adsorption equilibrium constants, K*, and micropore diffusivity, D, on the amount adsorbed were examined. The dependencies of adsorption equilibrium constants, K*, and micropore diffusivities, D, for benzene, toluene and m-xylene, on the molarity of benzene over a range of temperature and pressure were obtained. Experimental results were simulated using the “Stop & Go” method as well as by molecular simulation.